Geological Characteristics and Exploration Prospect of Black Shale in the Dongyuemiao Member of Lower Jurassic, the Eastern Sichuan Basin, China - Wei, Guodong; Wang, Wei; Feng, Liang; Tan, Xiucheng; Yu, Chuan; Zhang, Hualian; Zhang, Zhiping; Wang, Shengxiu (Frontiers in Earth Science, 2021)
China has yielded huge commercial production from the marine organic-rich shale but shows a slow exploration process in the lacustrine organic-rich shale. Multiple lacustrine shales in the Lower Jurassic of the eastern Sichuan Basin, rich in organic matters, are potential targets for shale hydrocarbon exploration and development. An investigation of the Dongyuemiao member, Lower Jurassic, was firstly conducted utilizing the macroscopic and microscopic analyses on outcrops and drilling cores to reveal the characteristics of sedimentary subfacies, mineral compositions, organic matter content and types, thermal maturity level, and reservoir quality. The dark shales in the Dongyuemiao member can be grouped into four general categories: shore, shallow, semi-deep, and deep lacustrine shales. The semi-deep and deep lacustrine shales generally have higher values in thickness (>20 m), average total organic carbon (TOC) content (>1.5 wt.%), and average porosity (>2%) relative to shore and shallow lacustrine shales. All four categories of shales primarily consist of type II kerogen and have thermal maturity levels exceeding the vitrinite reflectance value of 0.9–1.0% (or the Tmax of ∼440°C). Thermally powered pore generation generally promoted the pore system as indicated by the positive correlation between porosity and Tmax. Notably, the semi-deep lacustrine shale in the vicinity of the Qiyueshan Fault Zone shows abnormally high porosity and low oil saturation index (OSI) at Tmax>∼465°C potentially due to the promoted hydrocarbon expulsion through multiscale fractures. Except for the vicinity of the Qiyueshan Fault Zone, the semi-deep and deep lacustrine shales generally show the better exploration prospect relative to the shore and shallow lacustrine shales. Additionally, the high content of clay minerals (>40 wt%) reduced the brittleness of the semi-deep and deep lacustrine shales which may challenge the artificial hydraulic fracturing.